Causal Factors Influencing Apartment Rental Intention on Facebook Pages of Users in Bangkok and Its Vicinity - Wassaeng, Phattaraporn; Pankham, Sumaman (Arts of Management Journal, 2023)
This article aimed to 1) develop and validate a causal relationship model of apartment rental intention on Facebook pages of service users in Bangkok and its vicinity; and 2) to find causal factors influencing apartment rental intention on Facebook pages of service users in Bangkok and its vicinity. This study was quantitative research. The sample was 400 people who have rented apartments on Facebook pages and lived in Bangkok and its vicinity. The tools used in the research was online questionnaires. The statistics used in data analysis were frequency, percentage, confirmatory factor analysis and structural equation model. The results indicated that the development of the causal relationship models consisted of four components: 1) reputation 2) satisfaction 3) trust and 4) purchase intention, and the model was consistent with the empirical data to a great extent. The statistic showed CMIN/df = 2.02, GFI = 0.90, AGFI = 0.90, SRMR = 0.02 and RMSEA = 0.05. The final prediction coefficient was 0.81, indicating that the variables in the model could explain the variance of rental intention for 81 percent of apartments on Facebook pages. It was found that trust, reputation and satisfaction were respectively influenced by rental intention. The results of this research are beneficial to entrepreneurs or those who are interested in the apartment rental business. It can be used as a guideline to further develop the business and increase the efficiency of apartment rental services on the Facebook page.